Loneliness as a mediator of the relationship of social cognitive variables with depressive symptoms and quality of life in lung cancer patients beginning treatment. Issue 6 (3rd May 2019) - Hyland, Kelly A.; Small, Brent J.; Gray, Jhanelle E.; Chiappori, Alberto; Creelan, Ben C.; Tanvetyanon, Tawee; Nelson, Ashley M.; Cessna‐Palas, Julie; Jim, Heather S.L.; Jacobsen, Paul B.
Abstract: Objective: Loneliness, or the discrepancy between perceived and desired level of social connectedness, is an understudied but important psychosocial factor in cancer patients. The current study investigated the relationship between loneliness, depressive symptoms, quality of life, and social cognitive variables (eg, stigma, social constraint, and cancer‐related negative social expectations), and explored loneliness as a mediator of the relationship between social cognitive variables and depressive symptoms and quality of life in lung cancer patients beginning treatment. Methods: Patients within 3 months of beginning treatment for lung cancer completed measures of loneliness, depressive symptoms, quality of life, and social cognitive variables. Correlational, chi‐square, and hierarchical regression analyses evaluated relationships among variables. Bias‐corrected bootstrapping methods estimated the indirect effect and 95% confidence interval for mediation models. Results: Participants (n = 105, M = 65.5 years, 55% female) endorsed low to moderate levels of loneliness. Greater loneliness was associated with greater depressive symptoms and worse quality of life ( P 's < .001), and loneliness explained unique variance in depressive symptoms (F = 10.18, P  < .001, ΔR 2  = .06, Total R 2  = .35) and quality of life (F = 19.55, P  < .001, ΔR 2  = .05, Total R 2  = .52) after controlling for significant covariates. Greater stigma, social constraint, and cancer‐related negative social expectations were associated with greater loneliness and depressive symptoms and worse quality of life ( P 's < .001). Loneliness partially mediated the relationship of social cognitive variables with depressive symptoms and quality of life. Conclusions: Beyond its direct impact on clinically relevant outcomes, the experience of loneliness may be a mechanism by which social cognitive factors influence depressive symptoms and quality of life in lung cancer patients.